Cyber security in the open data: where is the equilibrium? - Zulhuda, Sonny (2017)
Governments in virtually all countries want better cybersecurity against cyber spying, but also seek the capacity for cyber espionage on others. Following reports of mutual cyber espionage between China and the United States, it was proposed that both countries agree to a policy of Mutually Assured Restraint (MAR). In 2015 both governments agreed to stop people in their countries from cyberspying in the other country for profit but exempted themselves as governments from this prohibition. A US investigation has also delved into allegations of Russian cyber involvement in the recent US presidential election. What can other countries learn from such experiences? IN this paper, the interplay between cybersecurity and open data policy in the Malaysian context is being discussed.